Ruminal Fermentation Pattern, Bacterial Community Composition, and Nutrient Digestibility of Nellore Cattle Submitted to Either Nutritional Restriction or Intake of Concentrate Feedstuffs Prior to Adaptation Period - Pinto, Ana C. J.; Bertoldi, Gustavo P.; Felizari, Luana D.; Dias, Evandro F. F.; Demartini, Breno L.; Nunes, Ana B. C. P.; Squizatti, Mariana M.; Silvestre, Antonio M.; Oliveira, Lucas F. R.; Skarlupka, Joseph H.; Rodrigues, Paulo H. M.; Cruz, Gustavo D.; et al. (Frontiers in Microbiology, 2020)
Beef cattle are key contributors to meat production and represent critical drivers of global agricultural economy. In Brazil, beef cattle are reared in tropical pastures and finished in feedlot systems, which includes a period where they adapt to high-concentrate diets. This adaptation period is critical to the success of incoming cattle, as they must adjust to both a new diet and environment. Incoming animals are typically reared on a variety of diets, ranging from poor quality grasses to grazing systems supplemented with concentrate. These disparate pre-adaptation diets present a challenge, and we sought to understand this process by evaluating adaptation of Nellore calves raised on either grazing on poor quality grasses or grazing systems supplemented with concentrate. Given that nutrient provisioning from the diet is the sole responsibility of the ruminal microbial community, we measured the impact of this dietary shift on feeding behavior, ruminal fermentation pattern, ruminal bacterial community composition (BCC), and total tract digestibility. Six cannulated Nellore bulls were randomly assigned to a replicated 3×3 Latin square design, and received a control, restriction, or concentrate diet. All cohorts were fed the same adaptation diet to mimic a standard feedlot. Ruminal BCC was determined using Illumina-based 16S rRNA amplicon community sequencing. We found that concentrate-fed cattle had greater dry matter intake (P<0.01) than restricted animals. Likewise, concentrate-fed cattle had greater (P=0.02) propionate concentration during the adaptation phase than control animals and a lower Shannon’s diversity (P=0.02), relative to the restricted animals. We also found that these animals had lower (P=0.04) relative abundances of Fibrobacter succinogenes when compared to control animals during pre-adaptation phase and lower abundances of bacteria within the Succinivibrio during finishing phase, when compared to the control animals (P=0.05). Finally, we found that animals previously exposed to concentrate were able to better adapt to high-concentrate diets when compared to restricted animals. Our study presents the first investigation of the impact of pre-adaptation diet on ruminal BCC and metabolism of bulls during the adaptation period. We suggest that these results may be useful for planning adaptation protocols of bulls entering the feedlot system and thereby improve animal production.